Cephalometric characteristics of patients with temporomandibular joint disorders: A radiographic cross-sectional study - Asim Mustafa Khan; Veena S Narayanan; Jaishankar Homberhalli Puttabuddi; Mangala Rakaraddi; Rachita Chengappa; Pradeep Kumar Vallurupalli (Wolters Kluwer Medknow Publications, 2014)
This article has being retracted as the article was previously published in the same journal.